2022
DOI: 10.3390/jcm11175239
|View full text |Cite
|
Sign up to set email alerts
|

Invasiveness of Ventilation Therapy Is Associated to Prevalence of Secondary Bacterial and Fungal Infections in Critically Ill COVID-19 Patients

Abstract: Superinfections are a fundamental critical care problem, and their significance in severe COVID-19 cases needs to be determined. This study analyzed data from the Lean European Open Survey on SARS-CoV-2-Infected Patients (LEOSS) cohort focusing on intensive care patients. A retrospective analysis of patient data from 840 cases of COVID-19 with critical courses demonstrated that co-infections were frequently present and were primarily of nosocomial origin. Furthermore, our analysis showed that invasive therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
1
10
2
Order By: Relevance
“…Similarly, Falcone et al (2020) reported high rates at 71.6% among patients with COVID-19 admitted to ICUs in participating Italian hospitals [ 64 ]. Our findings also contrast with those of Ghali et al (2021) in Tunisia where HAIs were seen in 35.1% of patients in ICU with COVID-19 [ 24 ], and with de Hesselle et al (2022) among patients critically ill in ICUs enrolled into the Lean European Open Survey on SARS-CoV-2-Infected Patients (LEOSS) study [ 27 ]. Secondary bacterial infections were documented in the critical phase in 40.4% of cases in this study, and secondary fungal infections in 14.6% of cases [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similarly, Falcone et al (2020) reported high rates at 71.6% among patients with COVID-19 admitted to ICUs in participating Italian hospitals [ 64 ]. Our findings also contrast with those of Ghali et al (2021) in Tunisia where HAIs were seen in 35.1% of patients in ICU with COVID-19 [ 24 ], and with de Hesselle et al (2022) among patients critically ill in ICUs enrolled into the Lean European Open Survey on SARS-CoV-2-Infected Patients (LEOSS) study [ 27 ]. Secondary bacterial infections were documented in the critical phase in 40.4% of cases in this study, and secondary fungal infections in 14.6% of cases [ 27 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings also contrast with those of Ghali et al (2021) in Tunisia where HAIs were seen in 35.1% of patients in ICU with COVID-19 [ 24 ], and with de Hesselle et al (2022) among patients critically ill in ICUs enrolled into the Lean European Open Survey on SARS-CoV-2-Infected Patients (LEOSS) study [ 27 ]. Secondary bacterial infections were documented in the critical phase in 40.4% of cases in this study, and secondary fungal infections in 14.6% of cases [ 27 ]. Other studies though have recorded appreciably higher rates with up to 68% of patients in ICUs acquiring secondary bacterial infections during their stay, principally secondary pneumonia [ 65 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…By a mathematical model, it is well known that the vaccination program has altered the course of COVID-19, reducing the related mortality already after the first year of vaccine program ( 34 ). Furthermore, the impact of MDR and fungal superinfections has increased from the beginning of the pandemic, severely afflicting the survival rate of critically ill COVID-19 patients ( 35 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…General information about the included studies is summarized( Table 1 ). 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 We focused on collecting some of the most common strains, such as Enterobacter, S. aureus , and Klebsiella pneumoniae . The results of eight studies were showed that 42% of the patients with COVID-19 were infected with MDR (95% confidence interval (CI), 0.23–0.61; P < 0.01) ( Figure 1 ).…”
mentioning
confidence: 99%